2017
DOI: 10.1155/2017/2147408
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Course to Lumbar Disc Resorption Patients and Predictive Factors Associated with Disc Resorption

Abstract: The long-term course to lumbar intervertebral disc herniation (LDH) patients receiving integrative Korean medicine treatment and predictive factors associated with disc resorption were investigated. LDH patients who received integrative Korean medicine treatment from February 2012 to December 2015 and were registered in the “longitudinal project for LDH on MRI” were included. Disc resorption amount was measured 3-dimensionally with disc degeneration and modic change levels on baseline and follow-up MRIs. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…In addition, integrative treatment consisting of electroacupuncture, Chuna therapy, cupping, physical therapy, and manual therapy used as treatment for disc diseases has been reported to induce absorption of herniated disc. [2327] We confirmed a case in which this treatment led to the resorption of discal cysts using this treatment regimen.…”
Section: Discussionsupporting
confidence: 69%
“…In addition, integrative treatment consisting of electroacupuncture, Chuna therapy, cupping, physical therapy, and manual therapy used as treatment for disc diseases has been reported to induce absorption of herniated disc. [2327] We confirmed a case in which this treatment led to the resorption of discal cysts using this treatment regimen.…”
Section: Discussionsupporting
confidence: 69%
“…Regarding lumbar MRI or CT findings, patients with FBSS with HNP showed a higher OR of achieving MCID in the NRS score for LBP. This is because integrative KM treatment in patients with lumbar disc herniation has a long-term effect on disc resorption [ 31 ], as well as improvement in pain and function [ 32 , 33 ]. The principle underlying the improvement of pain caused by lumbar disc herniation is suggested by previous studies on the effects of Shinbaro [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The resorption of LDHs after nonsurgical treatments has been widely reported since the first case in 1984. In these reports, the LDHs were characterized as decreasing or disappearing over time, and the nonsurgical treatments in these reports included bed rest, lumbar support, analgesics, oral steroids, non-steroidal anti-inflammatory drugs, epidural steroid injection, caudal epidural injections of local anesthetic, manipulation, hot back, ultrasound, electrotherapy, traction, exercises, Traditional Chinese Medicine and integrative Korean medicine[ 3 - 16 ]. However, which of these treatments are essential for promoting resorption and the time when resorption takes place remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of resorption varies in the existing reports depending on the different follow-up times. Lee reported the highest incidence of resorption of 96% with an average follow-up time of 341.38 ± 306.83 d[ 3 ]. Two studies reported no resorption with follow-ups of 45 d[ 4 ] and 20 d[ 5 ], suggesting that resorption should not be expected to occur too soon after nonsurgical treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation